Multicentric Castleman's disease in India - Does EBV rather than HHV8 play a role? - Viral Bhanvadia; Tanuja Shet; Vidya Rao; Sridhar Epari; Sumeet Gujral; Hasmukh Jain; Bhausaheb Bagal; Manju Sengar (Wolters Kluwer Medknow Publications, 2021)
Background and Aim: Multicentric Castleman's disease (MCD) is a rare lymphoproliferative disorder manifesting as multiple lymphadenopathy, multiorgan involvement, and inflammatory symptoms. This study aims at highlighting some unique features of MCD in Indian patients. Materials and Methods: These 17 patients from review of 78 cases of Castleman's disease (CD) diagnosed. Besides routine tissue sections were stained for Human Herpes Virus 8 latency associated nuclear antigen (HHV8-LANA) by immunohistochemistry (IHC) and Epstein Barr virus latent membrane protein (EBV-LMP) or Epstein Barr Virus by in situ hybridization (EBER-ISH). Result: The cases included Plasma cell variant (11 cases), mixed MCD (4 cases) and two concurrent MCD with large B cell lymphoma in HIV positive patients. Median age of disease onset was 47 years and female predominance was seen. Out of 15 MCD uncomplicated by lymphoma, 5 had POEMS (Polyneuropathy, organomegaly, endocrinopathy, myeloma protein, skin changes) and one also had TAFRO (Thrombocytopenia, anasarca, fever, marrow reticulin fibrosis, organomegaly, normal or slightly elevated immunoglobulin) syndrome. Out of 10 MCD without lymphoma, 2 cases showed few EBV positive large cells, both have features of POEMS. All 17 MCD cases were negative for HHV8-LANA IHC. Two HIV patients with MCD had large cell lymphoma, intrasinusoidal pattern, of which one was EBV positive. Though four relapses were seen, none died from disease. One of the two patients complicated by lymphoma died from disease. Conclusion: Indian patients with MCD show female preponderance and are negative for HHV8 but show EBV positive cells. This makes a case for role of EBV in etiopathogenesis of MCD in India.